Contraceptive discontinuation and switching behavior among family planning clinic clients in Dalhatu Araf Specialist Hospital, Lafia - Lohnan, Lucky C.; Chibuzo, Samuelson; Afolab-Oboirien, Khadijat; Edugbe, Adikpe E.; Odonye, Caleb E.; Bitrus, James (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Contraceptives are effective ways with which couples can limit or space the number of children they have. Several methods of contraception exist, both modern and traditional methods. Couples have a myriad of these from which to choose from. However, contraceptive discontinuation and switching are a reality. The dynamics of contraceptive use, discontinuation and switching are important markers of how well the programs are meeting the family planning needs of women and couples. The aim of the study was to ascertain the magnitude of women who wanted to discontinue or switch their present contraceptive methods and establish the reasons why. Methods: Our study was a cross sectional descriptive study of women attending the family planning clinic of Dalhatu Araf Specialist Hospital, Lafia over a 12 month period. A self-administered structured questionnaire was administered to the family planning clinic clients after obtaining a written informed consent. Results: Contraceptive discontinuation rate was 36.5%, and the switching rate was 5.2%. The commonest reasons for discontinuing contraception were; desirous of pregnancy (43%), side effects of method (28.2%), husband’s disapproval (16.7%), marital dissolution (4.2%), inconvenience of use (3.1%), failure of method (1.6%) and menopause (0.4%). The reasons for switching were also similar and include; side effects of the method (51.4%), inconvenience of use (16.2%), husband’s disapproval (8.1%), personal choice (5.4%) and marital dissolution (2.7%). Conclusions: We concluded that the contraceptive discontinuation rate was moderately high, while the switching rate was low. We recommend adequate counseling of clients before contraceptive uptake to forestall this.